Ischemic stroke in patients previously anticoagulated for non-valvular atrial fibrillation: Why does it happen? - Fernandes, L (2019)
Oral anticoagulants have proved to be highly effective in preventing atrial fibrillation (AF)-related strokes. The occurrence of stroke despite oral anticoagulation is unexpected and little is known about the mechanisms responsible. The aim of this study was to assess possible mechanisms for stroke occurrence, such as poor treatment adherence and inappropriate dosage, in patients chronically anticoagulated for AF.